Diseño de guía para la prevención de lesiones cervicales como estrategia de promoción de la salud a los trabajadores mediante la aplicación fisioterapéutica del método mindfulness - Ortega Lagos, Karen Yulieth; Rodríguez Guerrero, Laura Daniela (Universidad Antonio Nariño, 2021)
Neck pain and injuries are associated with muscle overload due to inappropriate habits and postures during the working day. They can cause the deterioration of the worker's quality of life, increase the costs derived from health care and absenteeism from work.